Application de Ia POO pour Ia conception d'un logiciel de simulation par elements finis en mise en forme des materiaux - Gelin, Jean-Claude; Paquie, Pascal; Walterthum, Luc (European Journal of Computational Mechanics, 1998)
The object oriented programming (OOP) applied to the definition of the structure of a finite element software for modelling material forming processes is presented. In a first part, a brief report on the evolution of programming techniques is given followed by the principles of OOP. Then the adequation of OOP is demonstrated for a simulation software used for material forming processes written in C++. The basic structure of the software is given and several examples are presented giving the possibilities of OOP for multi-analyses and multi-domains problems.